Syphilis and Subjectivity From the Victorians to the Present (Springer International Publishing, 2018)
This book demystifies the cultural work of syphilis from the late nineteenth century to the present. By interrogating the motivations that engender habits of belief, thought, and conduct regarding the disease and notions of the self, this interdisciplinary volume investigates constructions of syphilis that had a significant role in shaping modern subjectivity. Chapters draw from a variety of scholarly methods, such as cultural and literary studies, sociology, and anthropology. Authors unravel the representations and influence of syphilis in various cultural forms: cartography, medical writings, literature, historical periodicals, and contemporary popular discourses such as internet forums and electronic news media. Exploring the ways syphilitic rhetoric responds to, generates, or threatens social systems and cultural capital offers a method by which we can better understand the geographies of blame that are central to the conceptual heritage of the disease. This unique volume will appeal to students and scholars in the medical humanities, medical sociology, the history of medicine, and Victorian and modernist studies.